Correction to: ARIA 2016: Care pathways implementing emerging technologies for predictive medicine in rhinitis and asthma across the life cycle. Issue 1 (10th October 2019) - Bousquet, J.; van Hage, M.
Abstract : Following publication of the original article [1], the authors reported that one of the authors' names was spelled incorrectly. In this Correction the incorrect and correct author name are shown. In the author list of this Correction article, only the correct name of the affected author and the corresponding author are presented.